Material girls - Duff, Hilary, 1987-; Quaintance, John; Coolidge, Martha; Duff, Hilary, 1987-; Duff, Haylie, 1985-; Huston, Anjelica; Haas, Lukas, 1976-; Alonso, Maria Conchita; Spiner, Brent; Maverick Films; Rafter H Entertainment (Firm); Patriot Pictures; et al. (Postdam : FilmConfect Home Entertainment, 2009)
The daughters of a cosmetic company tycoon must learn what it's like without money and hired help, when a scandal in the company forces them to work for a living, while trying to clear their late father's name.
Originally released as a motion picture in 2006.
Director of photography, Johnny E. Jensen ; editor, Steven Cohen ; music, Jennie Muskett ; costume designer, Van Broughton Ramsey ; production designer, James Spencer.
Hilary Duff, Haylie Duff, Anjelica Huston, Maria Conchita Alonso, Lukas Haas, Brent Spiner.
DVD, region 2, widescreen; Dolby Digital 5.1 surround; aspect ratio 1.78:1.
English, dubbed German dialogue with optional German subtitles.
Keywords: Women -- Drama; Single women -- Drama; Fathers and daughters -- Drama; Comedy films; Feature films